Inactivation of the dimeric RappLS20 anti-repressor of the conjugation operon is mediated by peptide-induced tetramerization. Issue 14 (13th July 2020) - Crespo, Isidro; Bernardo, Nerea; Miguel-Arribas, Andrés; Singh, Praveen K; Luque-Ortega, Juan R; Alfonso, Carlos; Malfois, Marc; Meijer, Wilfried J J; Boer, Dirk Roeland
Abstract: Quorum sensing allows bacterial cells to communicate through the release of soluble signaling molecules into the surrounding medium. It plays a pivotal role in controlling bacterial conjugation in Gram-positive cells, a process that has tremendous impact on health. Intracellular regulatory proteins of the RRNPP family are common targets of these signaling molecules. The RRNPP family of gene regulators bind signaling molecules at their C-terminal domain (CTD), but have highly divergent functionalities at their N-terminal effector domains (NTD). This divergence is also reflected in the functional states of the proteins, and is highly interesting from an evolutionary perspective. RappLS20 is an RRNPP encoded on the Bacillus subtilis plasmid pLS20. It relieves the gene repression effectuated by RcopLS20 in the absence of the mature pLS20 signaling peptide Phr*pLS20 . We report here an in-depth structural study of apo and Phr*pLS20 -bound states of RappLS20 at various levels of atomic detail. We show that apo-RappLS20 is dimeric and that Phr*pLS20 -bound Rap forms NTD-mediated tetramers. In addition, we show that RappLS20 binds RcopLS20 directly in the absence of Phr*pLS20 and that addition of Phr*pLS20 releases RcopLS20 from RappLS20 . This allows RcopLS20 to bind the promotor region of crucial conjugation genes blocking their expression.